Equivalence of two methods for construction of regular continued C-fractions - Katsala, R. A.; Pahirya, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
A regular continued C-fraction is associated with a power series. The coefficients of this fraction are determined via either Hankel determinants or inverse derivatives. We prove the equivalence of these approaches to the construction of regular continued C-fractions.